a) Ta có: \(\int\limits_0^1 {2xdx} = {x^2}\left| \begin{array}{l}1\\0\end{array} \right. = 1\), \(2\int\limits_0^1 {xdx} = 2.\frac{{{x^2}}}{2}\left| \begin{array}{l}1\\0\end{array} \right. = 1\) nên \(\int\limits_0^1 {2xdx} = 2\int\limits_0^1 {xdx} \)
b) Ta có: \(\int\limits_0^1 {\left( {{x^2} + x} \right)dx} = \left( {\frac{{{x^3}}}{3} + \frac{{{x^2}}}{2}} \right)\left| \begin{array}{l}1\\0\end{array} \right. = \frac{1}{3} + \frac{1}{2} = \frac{5}{6}\)
\(\int\limits_0^1 {{x^2}dx} + \int\limits_0^1 {xdx} = \frac{{{x^3}}}{3}\left| \begin{array}{l}1\\0\end{array} \right. + \frac{{{x^2}}}{2}\left| \begin{array}{l}1\\0\end{array} \right. = \frac{1}{3} - 0 + \frac{1}{2} - 0 = \frac{5}{6}\)
Do đó, \(\int\limits_0^1 {\left( {{x^2} + x} \right)dx} = \int\limits_0^1 {{x^2}dx} + \int\limits_0^1 {xdx} \)
c) Ta có: \(\int\limits_0^3 {xdx} = \frac{{{x^2}}}{2}\left| \begin{array}{l}3\\0\end{array} \right. = \frac{{{3^2}}}{2} - 0 = \frac{9}{2}\); \(\int\limits_0^1 {xdx} + \int\limits_1^3 {xdx} = \frac{{{x^2}}}{2}\left| \begin{array}{l}1\\0\end{array} \right. + \frac{{{x^2}}}{2}\left| \begin{array}{l}3\\1\end{array} \right. = \frac{1}{2} - 0 + \frac{{{3^2}}}{2} - \frac{1}{2} = \frac{9}{2}\)
Do đó, \(\int\limits_0^3 {xdx} = \int\limits_0^1 {xdx} + \int\limits_1^3 {xdx} \)